REPESENTASI FEMINIS MARXIS DALAM FILM SUFFRAGETTE - Danadharta, Irmasanthi (Universitas 17 Agustus 1945 Surabaya, 2019)
This paper tries to describe the Marxist Feminist values that are embedded within themovie Suffragette. Suffragette is a movie created by Sara Gayron and was premiered bythe French cinema Pathé. Suffragette was inspired by a true story of the movement fromthe Radical Feminist group Suffragette led by Emmeline Pankhurst, in fighting for thewomen’s rights for political participation. Suffragette tells the story using the perspectiveof the main character Maud Watts, a laundry service worker who joined Pankhurst inraising the issue of sexual harassment and women’s rights to vote in front of theParliament; which mainly consists of upper class Caucasian men. This paper exhibits theinequality between the upper class and the domination of masculinity towards thelabors/female labors. This research adapt on Sara Mills’ Discourse Analysismethodology in order to provide description of the Marxist Feminist values which wasadopted within the character of Maud Watt, as the research subject, and the act ofresistance by Suffragettes as the object; in addition, placing the movie viewers as thereader and Sara Gavron as the writer. The values of Marxist Feminism were visiblethrough the scene which the character Maud Watts gave her testimony before the courtand within the Darby Horse Race scene which the group Suffragette performed theirprotest. The court scene showed the resistance from the female labor group, whichrepresents the rejection against the hegemonic masculinity values that’s projected by theupper class Caucasian men in parliament. In the final scene, the Darby, which wasconsidered as an activity for the elites and demonstrates masculine and competitivevalues, was chosen as a channel to demonstrate the labor class women’s resistance.Keywords : Representation, Marxist Feminism, Suffragette, Feminist Methodology, Movie.